A Pilot Study Showing Acute Inhibitory Effect of GLP‐1 on the Bone Resorption Marker CTX in Humans. (23rd August 2019) - Nissen, Anne; Marstrand, Simone; Skov‐Jeppesen, Kirsa; Bremholm, Lasse; Hornum, Mads; Andersen, Ulrik B; Holst, Jens Juul; Rosenkilde, Mette Marie; Hartmann, Bolette
ABSTRACT: Bones have been suggested to be a target for glucagon‐like peptide ‐1 (GLP‐1); however, studies of the effects on human bones so far have given diverging results. We hypothesized that GLP‐1, together with glucagon‐like peptide‐2 and glucose‐dependent insulinotropic polypeptide, plays a role in the gut–bone axis. We examined the acute effect of three GLP‐1 receptor ligands [GLP‐1 (7‐36)amide, GLP‐1 (9‐36)amide, and exenatide] on markers of bone remodeling. Eight healthy, normal‐weight participants, with a mean age of 24.3 years, were studied for 4 days in a double‐blinded, randomized clinical trial. Blood was collected before and after s.c. injection of GLP‐1 (7‐36)amide (1.5 nmol/kg), GLP‐1 (9‐36)amide (1.5 nmol/kg), exenatide (2.4 nmol/subject), or saline. Plasma was analyzed for bone markers and for osteoprotegerin (OPG), PTH, and IGF‐1 levels. All ligands were tested in vitro for their cAMP‐inducing activity on the human GLP‐1 receptor. GLP‐1 (7‐36)amide decreased CTX‐levels, compared with placebo (area under the curve [AUC] ±SD 0 to 120 min = –2143 ± 1294 % × min versus –883 ± 1557 % × min; p < 0.05). No difference was observed between placebo and GLP‐1 (9‐36)amide, or between placebo and exenatide, although exenatide had a similar potency as GLP‐1 (7‐36)amide for cAMP formation in vitro (EC50 of 0.093 and 0.054 nmol/L). However, exenatide reached maximum plasma concentration at 90 min versus 15 min for GLP‐1 (7‐36)amide, and plasma CTX was significantly decreased during the second hour of the study after exenatide injections compared with placebo (AUC ±SD –463.1 ± 218 % × min and –136 ± 91 % × min; p < 0.05). There was no effect of the injections on bone formation markers (P1NP and osteocalcin) or on OPG, PTH and IGF‐1 levels. In conclusion, we show that GLP‐1 receptor agonists, but not the primary metabolite GLP‐1 (9‐36)amide, decrease bone resorption, and suggest that GLP‐1 may be part of the gut–bone axis. © 2019 The Authors. JBMR Plus is published by Wiley Periodicals, Inc. on behalf of the American Society for Bone and Mineral Research.